2018
DOI: 10.1038/s41550-018-0508-y
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational lensing detection of an extremely dense environment around a galaxy cluster

Abstract: Galaxy clusters form at the highest density nodes of the cosmic web 1,2 . The clustering of massive halos is enhanced relative to the general mass distribution and matter beyond the virial region is strongly correlated to the halo mass (halo bias) 3 . Clustering can be further enhanced depending on halo properties other than mass (secondary bias) 4-7 . The questions of how much and why the regions surrounding rich clusters are over-dense are still unanswered [8][9][10][11][12][13] . Here, we report the analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 66 publications
(110 reference statements)
2
20
0
Order By: Relevance
“…At the same time it should be stressed that PSZ2G099 is sitting in a special region of the Universe, which was found to be about six times denser than the average density of the Universe at that redshift (Sereno et al 2018); its RH could therefore be unique. The effect of the large-scale environment (environment-bias; see Mao et al 2018, and ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time it should be stressed that PSZ2G099 is sitting in a special region of the Universe, which was found to be about six times denser than the average density of the Universe at that redshift (Sereno et al 2018); its RH could therefore be unique. The effect of the large-scale environment (environment-bias; see Mao et al 2018, and ref.…”
Section: Discussionmentioning
confidence: 99%
“…PSZ2G099 is a massive, M 500 = (6.84±0.48)×10 14 M (Planck Collaboration et al 2016) and hot, kT = 8.9 +2.8 −1.1 keV (Sereno et al 2018) cluster discovered through its Sunyaev-Zel'dovich (SZ) signal by the Planck satellite. Recently, the gravitational lensing signal of this cluster has been traced up to 30 Mpc from its centre implying that it sits in a very high-density environment, about six times denser than the average ΛCDM prediction at this redshift (Sereno et al 2018). The expected complex dynamics around this cluster make the discovery of a RH in this cluster particularly interesting.…”
Section: Introductionmentioning
confidence: 99%
“…This cut was originally proposed by Oguri et al (2012) based on the properties of the galaxies in the COSMOS catalogue (Ilbert et al 2009) to select galaxies at z 0.7, and has been subsequently tested and used by Covone et al (2014), Sereno et al (2017Sereno et al ( , 2018a. In particular, Sereno et al (2017) showed that the 97% of the galaxies with high quality spectroscopic redshifts selected by this cut in the CFHTLS-W1 and W4 fields have z spec > 0.63.…”
Section: Colour Selectionmentioning
confidence: 99%
“…However, the work in ref. 273 recently reported the first detection of an extremely dense environment around a massive galaxy cluster, PSZ2 G099.86 + 58.45, located at redshift z 0.616, from the PSZ2LenS [274] cluster sample. PSZ2LenS is a small but homogeneous and complete sample of 35 galaxy clusters, detected by the Planck mission in the sky regions observed by the CFHTLenS (Canada-France-Hawaii Telescope Lensing Survey) [275] and RCSLenS (Red Cluster Sequence Lensing Survey) [276].…”
Section: A New Challenge For the λCold Dark Matter Scenario: The Extremely Dense Environments Around Clusters Of Galaxiesmentioning
confidence: 99%